Análise do comportamento de variáveis eletromiográficas e cinemáticas nas subfases do supino paralímpico em atletas de elite - Silva, Bárbara Gama da (2019)
With the significant increase in the practice of the Paralympic Powerlifting sport, studies have been conducted to understand the mechanisms involved in the practice, thus assisting in the development of high performance fitness training programs. The main objective of this study is to verify the behavior of electromyographic and kinematic parameters of the eccentric and concentric phases of the Paralympic bench press movement in high performance athletes, so the RMS, Mean Frequency and Frequency Median (F50) variables were analyzed for the pectoralis major, triceps brachii and anterior deltoid. Participants were 4 females aged 23 to 48 years (mean 39.8 ± 11.2) and 6 males aged 18 to 41 years (mean 26.5 ± 8.0). To perform 3 attempts at 95% of the 1RM load, obeying the rules of the modality. For the analysis of the results, the graphs of displacement and velocity of the bar were plotted to identify the sub-phases of the movement. It was found that the RMS value of the pectoral and deltoid muscles presented higher activation values in all movement sub-phases. For the frequency domain variables, the triceps muscle presented high values especially in the concentric phase of the bench press movement suggesting that its firing rate is higher than that of the other muscles.